Encapsulation of propolis extracted with methylal in the chitosan nanoparticles and its antibacterial and cell cytotoxicity studies - Akbar Vaseghi; Reza Ashrafi Parchin; Kosar Rezaee Chamanie; Marc Herb; Hajar Maleki; Majid Sadeghizadeh (BMC, 2024)
Abstract In this study we develop novel type of antibacterial chitosan-propolis NPs to improve theantimicrobial activity against various pathogens. To this aim, we primarily extracted propolis with methylal and ethanol as green solvents and its encapsulation with chitosan NPs. The developed propolis loaded chitosan NPs indicated antimicrobial and anti-biofilm properties against various gram positive and negative. FTIR revealed the successful encapsulation of the propolis extract with Ethanol (PE) and Methylal (PM) into the chitosan nano career matrix. HPLC and GC-MASS also confirmed the presence of flavonoids and phenols compounds of propolis extracted with both solvents. In addition, we confirmed the total phenolic and flavonoid compounds in propolis by calorimetric method of Folin-Ciocalteu and aluminum trichloride complex formation assays, respectively. PE-CH and PM-CH were optimized regarding physicochemical properties such as particle size, zeta potential, and poly dispersity index (PDI) index. DLS and SEM micrographs confirmed a spherical morphology in a range of 360-420 nm with Z potential values of 30-48 mV and PDI of 0.105-0.166 for PE-CH and PM-CH, respectively. The encapsulation efficiency was evaluated using colorimetric analysis, with median values ranging from 90 to 92%. The MIC values within the range of 2 to 230 µg/ml and MBC values between 3 to 346 μg/ml against both gram-positive and negative bacteria. While both PE and PM showed a significant reduction in the number of E. coli, S. aureus, and S. epidermidis, the use of PE-CH and PM-CH led to a statistically significant and greater reduction in number of E. coli, S. aureus, and S. epidermidis strains on the biofilm, pre-formed biofilm and planktonic phases. Besides, the DPPH assay showed significant antioxidant activity for these NPs within the range of 36 to 92%. MTT assay for MHFB-1, HFF, L929, MDF, and MCF-7 cells exhibited statistically significant differences in each other that show the IC50 between 60-160 µg/ml for normal cells and 20 for cancer cells. Finally the present study indicated that both PM and PM-CH greater than PE and PE-CH in which contain high flavonoid and phenolic contents with a high antioxidation potential antioxidant properties, which could be beneficial for cell proliferation and antibiotic and anticancer applications.